1995
DOI: 10.1172/jci117703
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that the brain of the conscious dog is insulin sensitive.

Abstract: The aim of this study was to determine whether a selective increase in the level of insulin in the blood perfusing the brain is a determinant of the counterregulatory response to hypoglycemia. Experiments were carried out on 15 conscious 18-h-fasted dogs. Insulin was infused (2 mU/kg per min) in separate, randomized studies into a peripheral vein (n = 7) or both carotid and vertebral arteries (n = 8). This resulted in equivalent systemic insulinemia (84±6 vs. 86±6 jU/ml) but differing insulin levels in the hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
41
3
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 64 publications
4
41
3
1
Order By: Relevance
“…Circulating insulin appears to have no direct effect on glucose utilisation in the brain, despite recent observations in hypoglycaemic dogs and humans that the brain is sensitive to insulin [22,23]. In agreement with previous findings in dogs [24], brain glucose utilisation was of similar magnitude irrespective of the fall in circulating glucose from 4.8 to 2.4 mmol/l ( Table 1).…”
Section: Discussionsupporting
confidence: 88%
“…Circulating insulin appears to have no direct effect on glucose utilisation in the brain, despite recent observations in hypoglycaemic dogs and humans that the brain is sensitive to insulin [22,23]. In agreement with previous findings in dogs [24], brain glucose utilisation was of similar magnitude irrespective of the fall in circulating glucose from 4.8 to 2.4 mmol/l ( Table 1).…”
Section: Discussionsupporting
confidence: 88%
“…In our earlier experiments, we used high levels of insulin to create hypoglycemia and showed that complete vagal blockade failed to alter the counterregulatory response. Davis et al (9), however, have shown, using their head insulin infusion model, that in the presence of the same systemic glycemia (ϳ57 mg/dl) and insulinemia (ϳ85 U/ml), a selective increase in the insulin level in the head (85 vs. 195 U/ml) was associated with a marked increase in the sympathetic response to hypoglycemia. They subsequently concluded that the brain can directly sense the circulating insulin level.…”
Section: Discussionmentioning
confidence: 99%
“…The results of our experiments argue against a role for vagal afferents in the initiation of the counterregulatory response to insulin-induced hypoglycemia. On the other hand, Davis et al (9,10) demonstrated that during insulin-induced hypoglycemia in conscious dogs, the brain insulin level is a key determinant of the magnitude of the counterregulatory response, such that higher insulin levels markedly augment the sympathetic response to hypoglycemia. The concept that the insulin concentration can modify the counterregulatorry response to hypoglycemia has also been demonstrated in nondiabetic (11,12) and diabetic humans (13,14).…”
mentioning
confidence: 99%
“…12 Although during hypoglycemia different insulin infusion rates had no effect on the ACTH and cortisol response in the present study, previous studies 13 -15 provided evidence for a dose-dependent amplifying effect of insulin on HPA response to hypoglycemia. Moreover, Davis et al 16 demonstrated that a selective increase in the level of insulin in the blood perfusing the brain amplified the cortisol response to hypoglycemia in dogs, indicating that insulin directly acts on the brain. Taken together, the previous and present results provide strong evidence that hyperinsulinemia increases basal as well as hypoglycemia-stimulated HPA secretory activity.…”
Section: Discussionmentioning
confidence: 99%